2009
DOI: 10.1038/jcbfm.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells-Coupled tPA Prevents Impairment of Cerebral Vasodilatory Responses and Tissue Injury in Pediatric Cerebral Hypoxia/Ischemia through Inhibition of ERK MAPK Activation

Abstract: Babies experience hypoxia (H) and ischemia (I) from stroke. The only approved treatment for stroke is fibrinolytic therapy with tissue-type plasminogen activator (tPA). However, tPA potentiates H/I-induced impairment of responses to cerebrovasodilators such as hypercapnia and hypotension, and blockade of tPA-mediated vasoactivity prevents this deleterious effect. Coupling tPA to RBCs reduces its CNS toxicity through spatially confining the drug to the vasculature. Mitogen activated protein kinase (MAPK), a fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…6 Infusion of RBC-bound tPA in mice, rats and pigs has been shown to prevent thrombotic occlusion in the peripheral and cerebral vasculature, without the hemorrhagic and CNS toxicities seen with soluble nontargeted tPA. [6][7][8][21][22][23] Two major obstacles must be overcome to translate this new approach into preclinical and clinical development. First, for use as thromboprophylaxis, the respective agent should enjoy a prolonged circulation as a latent pro-drug and then be activated only when and where thrombi begin to form.…”
Section: Discussionmentioning
confidence: 99%
“…6 Infusion of RBC-bound tPA in mice, rats and pigs has been shown to prevent thrombotic occlusion in the peripheral and cerebral vasculature, without the hemorrhagic and CNS toxicities seen with soluble nontargeted tPA. [6][7][8][21][22][23] Two major obstacles must be overcome to translate this new approach into preclinical and clinical development. First, for use as thromboprophylaxis, the respective agent should enjoy a prolonged circulation as a latent pro-drug and then be activated only when and where thrombi begin to form.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rA2 plus low-dose tPA combination may improve recanalization and cerebral blood flow recovery. Third, despite clot lysis and reperfusion, experimental studies using advanced 'closed cranial window technique' have clearly shown that exogenous tPA may impair physiological responses of cerebral vasodilatation to hypoxia/ ischemia, and as well cause vasoconstriction after hypoxic/ischemic injury in a dose-dependent manner (Armstead et al, 2005(Armstead et al, , 2009Nassar et al, 2004). So by lowering tPA dose, the combination might eliminate tPA direct vasoactivity effect.…”
Section: Discussionmentioning
confidence: 99%
“…RBC/tPA circulate for many hours and incorporate into and rapidly dissolve newly formed, potentially occlusive clots from within (Murciano et al, 2003). Infusion of RBC/tPA in mice, rats, and pigs provides an effective short-term option to prevent thrombotic occlusion in diverse vascular systems, including the cerebral vasculature, without the hemorrhagic and CNS toxicity profile typically seen with free tPA (Murciano et al, 2003;Ganguly et al, 2005;Ganguly et al, 2006;Ganguly et al, 2007;Danielyan et al, 2008;Armstead et al, 2009).…”
mentioning
confidence: 99%